Regional hippocampal vulnerability in early multiple sclerosis: Dynamic pathological spreading from dentate gyrus to CA1. Issue 4 (13th January 2018) - Planche, Vincent; Koubiyr, Ismail; Romero, José E.; Manjon, José V.; Coupé, Pierrick; Deloire, Mathilde; Dousset, Vincent; Brochet, Bruno; Ruet, Aurélie; Tourdias, Thomas
Abstract: Background: Whether hippocampal subfields are differentially vulnerable at the earliest stages of multiple sclerosis (MS) and how this impacts memory performance is a current topic of debate. Method: We prospectively included 56 persons with clinically isolated syndrome (CIS) suggestive of MS in a 1‐year longitudinal study, together with 55 matched healthy controls at baseline. Participants were tested for memory performance and scanned with 3 T MRI to assess the volume of 5 distinct hippocampal subfields using automatic segmentation techniques. Results: At baseline, CA4/dentate gyrus was the only hippocampal subfield with a volume significantly smaller than controls ( p  < .01). After one year, CA4/dentate gyrus atrophy worsened (−6.4%, p  < .0001) and significant CA1 atrophy appeared (both in the stratum‐pyramidale and the stratum radiatum‐lacunosum‐moleculare, −5.6%, p  < .001 and −6.2%, p  < .01, respectively). CA4/dentate gyrus volume at baseline predicted CA1 volume one year after CIS ( R 2  = 0.44 to 0.47, p  < .001, with age, T2 lesion‐load, and global brain atrophy as covariates). The volume of CA4/dentate gyrus at baseline was associated with MS diagnosis during follow‐up, independently of T2‐lesion load and demographic variables ( p  < .05). Whereas CA4/dentate gyrus volume was not correlated with memory scores at baseline, CA1 atrophy was an independent correlate of episodic verbal memory performance one year after CIS ( ß  = 0.87, p  < .05). Conclusion: The hippocampal degenerative process spread from dentate gyrus to CA1 at the earliest stage of MS. This dynamic vulnerability is associated with MS diagnosis after CIS and will ultimately impact hippocampal‐dependent memory performance.